Consumption of pirated music and video CDs of UP Diliman students - Alfonso, Ginny Rosary
This paper examines the degree of consumption of pirated CDs and the factors related to the consumption such as the characteristics of U.P. students, the level of awareness about the problems encountered when using pirated CDs, the level of awareness of penalty in buying pirated CDs. The study was conducted among 270 U.P. Diliman students from August to October, 2003. The results reveal that majority of the students (83 percent either buy, rent or borrow pirated CDs. Students buy an average of 33 pirated CDs a year, roughly spending P 1842.00 for these. These were generally aware of the problems of poor quality of pirated CDs such as unclear copy, distorted sounds and unusual background noise, and that piracy is a violation of intellectual property rights. data analysis using correlation shows that student's allowance has a weak positive but highly significant relationship with the frequency and the quality of pirated CDs they buy. The low price of pirated copies is the most common reason cited by respondents for their purchase of pirated music and video CD's.